Alcohol Consumption and Its Health Impact - Rao, E. Venkata; Pattnaik, Sumitra (International Journal of Psychosocial Rehabilitation, 2019)
In this paper, the negative and the positive effects of alcohol on health are reviewed. It is first of all established facts that a high alcohol intake implies an increased risk of a large number of health outcomes, such as dementia, breast cancer, colorectal cancer, cirrhosis, upper digestive tract cancer and alcohol dependency. Second, it is justified that alcohol has beneficial effects for some individuals, especially with regard to prevention of thrombosis of the heart. The public health relevance of these results is considered. A broader public health message of the beneficial effects of alcohol does not seem to be of interest in Western societies, where only a very small fraction of the population are non-drinkers and may have very good reasons therefore. Because international differences in drink definitions also exist, comparing studies from different countries is difficult. The development of a universal definition of moderate drinking is hampered further by variations in the way alcohol consumption levels and drinking patterns are being assessed (i.e., the survey methods and assessment modes used). Despite these problems, definitions of moderate drinking and drinking guidelines have been developed in the countries.